Developmental biology, polymorphism and ecological aspects of Stiretrus decemguttatus (Hemiptera, Pentatomidae), an important predator of cassidine beetles - Paleari, Lucia Maria [UNESP] (Sociedade Brasileira de Entomologia, 2013)
Developmental biology, polymorphism and ecological aspects of Stiretrus decemguttatus (Hemiptera, Pentatomidae), an important predator of cassidine beetles. Stiretrus decemguttatus is an important predator of two species of cassidine beetles, Botanochara sedecimpustulata (Fabricius, 1781) and Zatrephina lineata (Fabricius, 1787) (Coleoptera, Cassidinae), on the Marajó Island, Brazil. It attacks individuals in all development stages, but preys preferentially on late-instar larvae. Its life cycle in the laboratory was 43.70 ± 1.09 days, with an egg incubation period of six days and duration from nymph and adult stages of 16.31 ± 0.11 and 22.10 ± 1.67 days, respectively. The duration of one generation (T) was 12.65 days and the intrinsic population growth rate (r) 0.25. These data reveal the adjustment of the life cycle of S. decemgutattus with those of the two preys, but suggest greater impact on Z. lineata. However, no preference over cassidine species was shown in the laboratory. Up to 17 different color patterns can be found in adults of S. decemguttatus, based on combinations of three basic sets of color markings. Some of them resemble the markings of chrysomelids associated with Ipomoea asarifolia (Convolvulaceae) and are possibly a mimetic ring. Three color patterns were identified in nymphs, none of which was associated with any specific adult color pattern.
Keywords: Asopinae; color pattern; Ipomoeae asarifolia; life table; predation